Hypnotherapy as a method of smoking cessation: a systematic review - Andrean, Jessie; Rahmaniati Makful, Martya (Universitas Gadjah Mada, 2022)
Purpose: Hypnotherapy is a method to stop smoking. But the effectiveness needs to be proven. Methods: a systematic review was conducted on articles published between 2012-2022 that examined hypnotherapy as a smoking cessation intervention. Results: four relevant studies were obtained. Two studies discussed the effectiveness of hypnotherapy over relaxation and nicotine replacement therapy (NRT). One study examined the effect of individual hypnosis susceptibility on the effectiveness of hypnotherapy. Finally, the study discusses the effect of brain waves on hypnotherapy through EEG assessment. Conclusion: Hypnotherapy intervention is superior to NRT but not superior to the relaxation method. Individuals with higher susceptibility are proven to have more influence on hypnotherapy interventions. Hypnotherapy has been shown to affect brain wave activity through EEG assessment. Further research is needed regarding the effectiveness of hypnotherapy on various population characters.